58 Real-life single-centre experience of Tocilizumab-associated neutropenia in children with juvenile idiopathic arthritis (JIA). (22nd November 2019) - Foley, Charlene; Fearon, Ursula; Obaidi, Muthana Al
Abstract : Background: Tocilizumab, approved for treatment of children with Systemic-onset-JIA (SoJIA) and polyarticular-JIA (pJIA) is efficacious and well-tolerated. Transient neutropenia is a side-effect of treatment. Aim: Chart-review of children treated with Tocilizumab to report on Tocilizumab-associated-neutopenic-episodes. Methods: Retrospective review of patients receiving Tocilizumab (January 2010-January 2019). Patients with extended-oligoarticular-JIA (ExO-JIA), pJIA and SoJIA reviewed in more detail to ascertain frequency of neutropenia and related-factors. For analysis, ExO-JIA and pJIA were combined to create an ExO/pJIA group. Neutropenia defined as neutrophils<1.5, severe-neutropenia<1.0. Statistical analysis was performed using the Mann-Whitney-U and Chi-Square tests. Results: Sixty-eight children (60%female) attending the rheumatology-department at GOSH are receiving Tocilizumab. Of these, 53 (78%) have a diagnosis of ExO-JIA (n=10), pJIA (n=12) or SoJIA (n=31). Disease duration pre-commencement of Tocilizumab was 2.9years(0.1–11). Children with SoJIA were commenced on Tocilizumab significantly (p<0.001) earlier in their disease course than children with ExO/pJIA (1.5years, 0.1–7.4 versus 6.5years, 0.4-11). Median time to first neutropenia was 0.5years(0.1-3.2). No significant pattern in time from commencing Tocilizumab to developing first neutropenia was observed. Recurrent neutropenia (i.e.>2episodes) occurred in 38% (20/53) and was significantly more common in SoJIA (p<0.05). All children with ExO/pJIA experienced a total of 2-3 neutropenic-episodes, significantly less (p<0.05) than the recurrence-rate in children with SoJIA (average7-episodes, 2-17). Severe neutropenia occurred in 65% (n=13) and was significantly (p<0.001) more frequent in SoJIA (n=11, 85%). In those with recurrent-neutropenia, no significant correlation was identified between risk of neutropenia and interval between doses, dose (mg/kg) received, concurrent Methotrexate, duration on Tocilizumab or number of alternative treatments received pre-Tocilizumab. Seventeen-children (32%) taking Tocilizumab had a documented infection. No relationship between neutropenia and risk of infection was identified. Conclusion: Tocilizumab-associated neutropenia is more frequent, severe and recurrent in SoJIA. Neutropenia can occur at any stage in the treatment-course. Clinicians should consider long-term blood-monitoring pre-Tocilizumab, especially for those with SoJIA.